2005
DOI: 10.1037/0735-7044.119.1.118
|View full text |Cite
|
Sign up to set email alerts
|

Sex, Age, and Training Modulate Spatial Memory in the Rhesus Monkey (Macaca mulatta).

Abstract: The authors tested 90 rhesus monkeys (Macaca mulatta) on a task of spatial memory, the spatial Delayed Recognition Span Test. The results showed that performance declined significantly with age, males had greater scores than females, and the rate of apparent decline with age was greater in males than in females. Both working and reference memory declined with age, but only working memory showed sex differences. The authors compared these data with that of 22 monkeys who were trained on a simpler version of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
46
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 105 publications
(121 reference statements)
8
46
0
Order By: Relevance
“…From such findings, it would be predicted that corresponding age by gender interactions would be found in behavioral data and, indeed, greater age-related cognitive decline in males than in females has been observed in both cross-sectional and longitudinal studies (e.g., Barrett-Connor & Kritz-Silverstein, 1999;Larrabee & Crook, 1993;Meyer et al, 1999;Rowe, Turcotte, & Hasher, 2004;Wiederholt et al, 1993;Zelinski & Stewart, 1998). Interestingly, similar results have been found in two studies of spatial memory in rhesus monkeys (Lacreuse et al, 2005;Lacreuse, Herndon, Killiany, Rosene, & Moss, 1999), suggesting that biological rather than sociocultural factors may underlie the gender differences in age-related decline.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…From such findings, it would be predicted that corresponding age by gender interactions would be found in behavioral data and, indeed, greater age-related cognitive decline in males than in females has been observed in both cross-sectional and longitudinal studies (e.g., Barrett-Connor & Kritz-Silverstein, 1999;Larrabee & Crook, 1993;Meyer et al, 1999;Rowe, Turcotte, & Hasher, 2004;Wiederholt et al, 1993;Zelinski & Stewart, 1998). Interestingly, similar results have been found in two studies of spatial memory in rhesus monkeys (Lacreuse et al, 2005;Lacreuse, Herndon, Killiany, Rosene, & Moss, 1999), suggesting that biological rather than sociocultural factors may underlie the gender differences in age-related decline.…”
Section: Introductionsupporting
confidence: 82%
“…There have also been occasional reports of greater age-related cognitive decline in females than in males (Brayne, Gill, Paykel, Huppert, & O'Connor, 1995, in the over-75s; 2 out of 8 tasks in Meinz & Salthouse, 1998). As noted by Lacreuse et al (2005), there may be a number of explanations for this mixed pattern of results, including population biases and the use of different tasks, age ranges, selection methods, and so on (see also Raz, 2000). For example, the greater longevity of females by approximately seven years (Hayflick, 1996) may have resulted in more positively selected males (because they are the survivors) than females, particularly in studies of very old adults (Singer et al, 2003; see also Perls, 1995;Perls, Morris, Ooi, & Lipsitz, 1993;Stewart, Zelinski, & Wallace, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Maylor et al (2007) tested a large sample of subjects (almost 200,000) with various tasks, and found a generally steeper age-related decline in response accuracy for males than females, while the opposite was found for response speed. The study of Lacreuse et al (2005) in non-human primates showed higher male performance in spatial working memory at a young age and a greater decline with age for males than for females.…”
Section: Introductionmentioning
confidence: 96%
“…Kimura, 1992). As concluded by Lacreuse et al (2005), the results of studies focusing on the relation of sex-and age-related differences to cognitive decline are inconsistent. While some investigations suggest that sex differences remain largely constant up to old age (Herlitz et al, 1997;Larrabee and Crook, 1993), others concluded that sex differences disappear at older age (Dollinger, 1995;Herman and Bruce, 1983;Robert and Tanguay, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Complex multi-tasking ("walking while memorizing") also declines progressively across middle age (Li et al 2001). The rhesus monkey also shows mild progressive cognitive changes from maturation through middle age into old age, in spatial memory (delayed recognition) (Lacreuse et al 2005) and executive function (Moore et al 2006); also see chapter by Morrison in this issue. A small sample of great apes (chimpanzees and orangutans) showed similar age trends for other cognitive tests (Anderson et al 2007(Anderson et al , 2005.…”
Section: Primate Neurobiologymentioning
confidence: 99%